2010
DOI: 10.1124/mol.110.069492
|View full text |Cite
|
Sign up to set email alerts
|

Verapamil Block of T-Type Calcium Channels

Abstract: Verapamil is a prototypical phenylalkylamine (PAA), and it was the first calcium channel blocker to be used clinically. It tonically blocks L-type channels in the inner pore with micromolar affinity, and its affinity increases at depolarized membrane potentials. In T-type calcium channels, verapamil blocks with micromolar affinity and has modestly increased affinity at depolarized potentials. We found that a related PAA, 4-desmethoxyverapamil (D888), is comparable with verapamil both in affinity and in state-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(56 citation statements)
references
References 26 publications
3
51
0
2
Order By: Relevance
“…[ 125 I]Alb uptake. The same was true of verapamil, the L-and T-type Ca 1 channel blocker (Bergson et al, 2011), which can also inhibit P-glycoprotein, an ATP-dependent drug transport protein (Schinkel, 1999). Albumin-binding proteins, such as endothelial membrane-associated gp60 (albondin) (Schnitzer, 1992), use caveolae-dependent mechanisms to transport albumin from peripheral blood vessel lumen to interstitium and are inhibited by filipin (Schnitzer et al, 1994;Tiruppathi et al, 1997), a cholesterol-binding agent that inhibits caveolaedependent transcytosis (Schnitzer et al, 1994).…”
Section: Brain Uptake Of Intranasal Albuminmentioning
confidence: 98%
“…[ 125 I]Alb uptake. The same was true of verapamil, the L-and T-type Ca 1 channel blocker (Bergson et al, 2011), which can also inhibit P-glycoprotein, an ATP-dependent drug transport protein (Schinkel, 1999). Albumin-binding proteins, such as endothelial membrane-associated gp60 (albondin) (Schnitzer, 1992), use caveolae-dependent mechanisms to transport albumin from peripheral blood vessel lumen to interstitium and are inhibited by filipin (Schnitzer et al, 1994;Tiruppathi et al, 1997), a cholesterol-binding agent that inhibits caveolaedependent transcytosis (Schnitzer et al, 1994).…”
Section: Brain Uptake Of Intranasal Albuminmentioning
confidence: 98%
“…Moreover, it has been reported that verapamil blocks T-type voltage-dependent calcium channels 30) . In the future, we will clarify the details of the influx of calcium ions into C2C12 cells during depolarization, using not only verapamil but also another type of calcium channel blocker.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, verapamil is used in clinical setting to terminate cardiac arrhythmias. 41,42 It is reported that calcium antagonists promote a change in cell shape from bipolar to spherical. The mechanism by which this is accomplished remains unknown.…”
Section: Primary Outcomes On Mechanism Of Actionmentioning
confidence: 99%